Lgr5 positive stem cells sorted from small intestines of diabetic mice differentiate into higher proportion of absorptive cells and Paneth cells in vitro. (30th June 2015) - Zhong, Xian‐Yang; Yu, Tao; Zhong, Wa; Li, Jie‐Yao; Xia, Zhong‐Sheng; Yuan, Yu‐Hong; Yu, Zhong; Chen, Qi‐Kui
<x xml:space="preserve">Abstract</x> Intestinal epithelial stem cells (IESCs) can differentiate into all types of intestinal epithelial cells (IECs) and Leucine‐rich repeat‐containing G protein‐coupled receptor 5 (Lgr5) is a marker for IESC. Previous studies reported enhanced proliferation of IECs in diabetic mice. In this study, the in vitro differentiation of Lgr5 positive IESCs sorted from diabetic mice was further investigated. The diabetic mouse model was induced by streptozotocin (STZ), and crypt IECs were isolated from small intestines. Subsequently, Lgr5 positive IESCs were detected by flow cytometry (FCM) and sorted by magnetic activated cell sorting (MACS). Differentiation of the sorted IESCs was investigated by detecting the IEC markers in the diabetic mice using immunostaining, quantitative real‐time reverse–transcription polymerase chain reaction (qRT–PCR), and Western blot analysis, which was compared with normal mice. We found that the proportion of Lgr5 positive cells in the crypt IECs of diabetic mice was higher than that of control mice (P < 0.05). Lgr5 positive IESCs could be significantly enriched in Lgr5 positive cell fraction sorted by MACS. Furthermore, the absorptive cell marker sucrase‐isomaltase (SI) and the Paneth cell marker lysozyme 1 (Lyz1) were more highly expressed in the differentiated cells derived from Lgr5 positive IESCs of diabetic mice in vitro (P < 0.05). We demonstrate that the number of Lgr5 positive IESCs is significantly increased in the small intestines of STZ‐induced diabetic mice. Lgr5 positive IESCs sorted from the diabetic mice can differentiate into a higher proportion of absorptive cells and Paneth cells in vitro. We characterized the expression of Lgr5 in the small intestine of diabetic mice, and sorted Lgr5 positive intestinal epithelial stem cells (IESCs) for investigating their differentiation in vitro. We proved that the quantity of Lgr5 positive IESCs was significantly increased in the small intestines of diabetic mice. IESCs sorted from the diabetic mice can differentiate into a higher proportion of absorptive cells and Paneth cells in vitro.